Hydroxychloroquine in the primary thrombosis prophylaxis of antiphospholipid antibody positive patients without systemic autoimmune disease. (March 2018) - Erkan, D; Unlu, O; Sciascia, S; Belmont, H M; Branch, D Ware; Cuadrado, M J; Gonzalez, E; Knight, J S; Uthman, I; Willis, R; Zhang, Z; Wahl, D; et al.
Objective: The objective of this study was to determine the efficacy of hydroxychloroquine (HCQ) in the primary thrombosis prevention of antiphospholipid antibody (aPL)-positive patients with no other systemic autoimmune diseases. Methods: Under the auspices of Antiphospholipid Syndrome Alliance for Clinical Trials and International Networking, a multicenter, international, randomized controlled trial (RCT) was initiated, in which persistently aPL-positive but thrombosis-free patients without systemic autoimmune diseases were randomized to receive HCQ or no treatment in addition to their standard regimen. The primary objective was the efficacy of HCQ in preventing the first thrombosis. The secondary objectives were the thrombosis incidence rate, and the effects of HCQ on aPL profile and mortality rate. Patients were risk-stratified based on antiplatelet agent use. The goal was to follow patients every 6 months for 5 years. Results: We recruited 20 persistently aPL-positive patients (female: 19, mean age: 46.6 ± 9.9 years, and baseline antiplatelet medication: 14); 9/20 were randomized to HCQ. During the mean follow-up of 1.7 years, no patients developed thrombosis or a serious adverse event. The study was terminated early due to the low recruitment rate, exacerbated by the prolonged manufacturing shortage and significant price increase of HCQ in the United States. Conclusion: Given that a small number of patients with a relatively short follow-up were enrolled in our RCT, and no patients developed thrombosis, we cannot accurately assess the effectiveness of HCQ for primary thrombosis prevention in persistently aPL-positive patients with no other systemic autoimmune diseases. Our experience suggests that conducting an international RCT, especially without pharmaceutical support, is an extremely challenging undertaking.